2021
DOI: 10.1002/pc.26016
|View full text |Cite
|
Sign up to set email alerts
|

Abrasive wear and dynamic–mechanical behavior of marble dust filled bagasse fiber reinforced hybrid polymer composites

Abstract: The present study investigated the influence of waste materials on physico‐mechanical, dynamic mechanical, and abrasive wear behavior of polymer composites. The composites were manufactured by varying the waste bagasse fiber (2.5, 5, 7.5, and 10 wt%) in fixed marble dust (15 wt%) filled epoxy resin. The void content of the composite found to decrease, whereas density, impact energy, and flexural strength were found to increase with the increase of waste bagasse fiber loading. The hardness and tensile strength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…This is true for randomly oriented short basalt fibre polymer composites. Considering the recent literature, hybrid composites comprised of carbon/basalt/epoxy showed better fracture strain and tensile strain as compared to carbon fibre epoxy composites; however, the tensile properties were reduced [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. These findings suggested that the arrangement of carbon/basalt fibre in the composite plays a crucial role in enhancing composites’ strength [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is true for randomly oriented short basalt fibre polymer composites. Considering the recent literature, hybrid composites comprised of carbon/basalt/epoxy showed better fracture strain and tensile strain as compared to carbon fibre epoxy composites; however, the tensile properties were reduced [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. These findings suggested that the arrangement of carbon/basalt fibre in the composite plays a crucial role in enhancing composites’ strength [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…At a fixed percentage of waste marble dust (15 wt. %), changing the bagasse fibre weightage to 7.5% improved the mechanical and physical properties of composites [ 31 ]. Not only the mechanical properties but also the wear performance, thermal characteristics, and fire retardancy of the composite were found to be enhanced by the inclusion of marble dust in fibre polymer composites [ 1 , 20 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…11 In this regard, natural fibers, that is, hemp, jute, banana, cotton, sisal, etc., have been successfully utilized as reinforcement by various researchers and scientists. 12,13 Cotton fiber is also a natural type of fiber which is used in textile industries for centuries. Dry weather harvested cotton fiber cultivated in the northern and southern hemispheres from the decades.…”
Section: Introductionmentioning
confidence: 99%
“…Rubbers usually have low thermal conductivity about 0.10-0.23 W/m K. [5][6][7] Thermally conductive fillers such as boron nitride (BN) and carbon nanotube (CNT) are added into rubbers to prepare thermally conductive rubbers. [8][9][10] Liu et al found that the thermal conductivity of silicone rubber increased by 30% after the addition of 14% BN nanosheet.…”
Section: Introductionmentioning
confidence: 99%
“…[14] The hollow glass microsphere/ nitride particle ratio and filler surface modification of significantly affected the thermal conductivity, dielectric constant and loss of low-density polyethylene. [15] Rubbers with wide damping temperature range and high damping factor (tan δ value) are an important development direction, [4,16,17] requiring a tan δ value over 0.3 in the temperature range of 60-80 C. [18,19] The damping factor of most rubbers is relatively low, and their effective damping temperature range is 20-40 C. [7,20] The damping properties of most rubbers cannot meet high requirements of applications. [21,22] Chen et al prepared chlorinated butyl rubber (CIIR)/terpene resin/carbon black damping material.…”
Section: Introductionmentioning
confidence: 99%